In - Chrisman, Kent (Thomson Delmar Learning, 2008)
In the Field combines readings, resources, and field assignments for various levels of students. Content is often presented in checklist format to encourage students to reflect on what they have learned, and to better the retention of the material. Applicable readings, suggested resources, and field assignments allow students to observe and participate in what they have learned, and will remain a resource as students transition to professional teaching roles